2013
DOI: 10.1179/2046905513y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of rectal tympanic and axillary thermometry in febrile children under 5 years of age in Nigeria

Abstract: Mean (SD) rectal temperature was 38.8 (0.7)°C, and mean (SD) tympanic and axillary temperatures were 38.7 (0.7)°C and 38.1 (0.7)°C, respectively. There was no significant difference between rectal and tympanic temperatures (P = 0.14), and a strong correlation was identified between values from these two sites (r = 0.91). At 91.5%, the sensitivity of tympanic thermometry in determining fever was higher than that of axillary measurements (54.0%). A mathematical relationship was demonstrated between rectal/tympan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…2,25,48 So it is suitable to decrease the cutoff of fever diagnosed by tympanic thermometry. Many studies have reported that temperature measured by tympanic thermometry was always 0.6°C to 0.2°C less than rectal temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,25,48 So it is suitable to decrease the cutoff of fever diagnosed by tympanic thermometry. Many studies have reported that temperature measured by tympanic thermometry was always 0.6°C to 0.2°C less than rectal temperature.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Accurate determination and detection of fever is essential in the appropriate treatment of pediatric population. [1][2][3][4][5] Accurate determination and detection of fever is essential in the appropriate treatment of pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other studies reported that the temperature of the tympanic membrane had a 67-76% sensitivity for detecting fever in children aged 6 months -6 years and there was no significant difference between the results of temperature measurements between the right and left ear (0.019 -0.2˚C). 3,[28][29][30] To minimize measurement errors, axillary skin must be dry. The precision of axillary temperature measurement for detecting fever is affected by peripheral vasoconstriction at the initial onset of fever, sweating, and evaporation resulting in lower skin temperature compared to the actual body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Core temperature is the gold standard for temperature measurement [3]. However, core temperature measurements, such as pulmonary artery and lower esophagus measurement, are invasive and requires specialized equipment, therefore, are unpractical for daily clinical practice [3,6]. Ideally, body temperature measurement should be noninvasive, accurate, pain-free, cost-effective and timeefficient [3,7,8].…”
Section: Introductionmentioning
confidence: 99%